The equivalence between the Mann and Ishikawa iterations dealing with generalized contractions - B. E. Rhoades; Ştefan M. Şoltuz (International Journal of Mathematics and Mathematical Sciences)
We show that the Mann and Ishikawa iterations are equivalently used to approximate fixed points of generalized contractions.